Paul Rusch in postwar Japan : Evangelism, rural development, and the battle against communism - McDonald, Andrew T.; McDonald, Verlaine Stoner (The University Press of Kentucky, 2018)
This text describes the remarkable life of Paul Rusch, a Kentuckian who went to Japan after the Great Kanto Earthquake.